Effect of integrated yoga on mental health and mindfulness of adolescents in the postpandemic period: A randomized control trial - Ashween Bilagi; Sony Kumari; M. Archana (Yoga-Mimamsa)
Introduction: The COVID-19 pandemic has profoundly disrupted the lives of adolescents, leading to significant impacts on their physical and mental health. Adolescents are particularly vulnerable to psychological stress and anxiety, which can have long-term consequences on their well-being. By combining physical postures (Asanas), breathing practices (Pranayama), and meditation, yoga has been shown to improve both physical and mental health. This study investigates the effects of integrated yoga on mindfulness and mental well-being in adolescents during the postpandemic era. Methods: A randomized control trial was conducted with 80 adolescent participants, who were randomly allocated into yoga and control groups (1:1 ratio). The yoga group was given 60 min of integrated yoga, 6 days weekly for a month. Mindfulness, mental well-being, depression, anxiety, and stress along with anthropometric and vital parameters were assessed before and after the intervention. Results: The demographic characteristics of both groups were well-matched across gender, age, religion, and school type. We had one dropout in each group, we analyzed 39 in each group with 19 males and 20 females in both groups. The month long integrated yoga demonstrates significant improvement in mental well-being and mindfulness while it also reduced depression, anxiety, stress, and waist–hip ratio compared to the control group. However, it did not show any significant improvement in other anthropometry and vital parameters. Conclusion: The present study has examined the role of yoga in promoting the mental well-being and mindfulness of adolescents who experienced death or hospitalization of a family member during the COVID-19 pandemic period.